Analisis kawasan hutan dan tutupan hutan pada tiga daerah aliran sungai di Kabupaten Manokwari - Haerul Arifin; Charlie D. Heatubun; Wahyudi Wahyudi (Program Pascasarjana Universitas Papua, 2019)
Law number 41 of 1999 concerning Forestry mandates to maintain the area of ​​forest area and forest cover for each rivers at least 30% of the total area, with a proportional distribution. The purpose of this study was to determine the area and percentage of the area and forest cover in the three watersheds, Arui, Prafi, and Wosi, in Manokwari District, analyze the composition, distribution, and changes in the area and forest cover, and describe the factors that influence these changes. this uses descriptive methods with quantitative analysis techniques. Data collection and analysis is done spatially using ArcGIS / ArcMap 10.1 software. The research variables consisted of area and forest cover in the watershed, composition, distribution, and change in the area and forest cover, area of ​​forest cover inside and outside the area expressed in hectares (ha) and percent (%), as well as factors that influence changes in the area and forest cover. The results showed that until 2016, the percentage of forest area to the total watershed for the two watersheds (Arui and Prafi) was still above 30%, while the Wosi watershed was only 14.79%, but the percentage of forest cover for the three watersheds was still above 30% The composition of the Arui and Prafi Watershed Forest Areas is dominated by Permanent Forests, whereas the Wosi Watershed is dominated by convertible Production Forests. In the Arui and Prafi watersheds, the distribution of the forest area is more concentrated in the upstream area and is dominated by primary forest, while the Wosi watershed is only in a portion of the upstream area with a predominance of secondary forest. During 2006 - 2016, the largest deforestation occurred in the Arui watershed (4.71% at a rate of 121.80 ha / year), conversely the highest forest degradation occurred in the Wosi watershed (39% at a rate of 5.31 ha / year). The dominant factor causing the change in the area in the three watersheds is thought to be a factor in partial change of forest area designation and Changes in Spatial Planning for the Provinces of West Papua and Manokwari in 2013-2033. Furthermore, population growth and land conversion to oil palm plantations, both by companies and communities, are the dominant factors causing deforestation.